Enantiospecific pharmacokinetic studies on ketoprofen in tablet formulation using indirect chiral HPLC analysis - Valliappan, Kannappan; Kannan, Kamarajan; Sivakumar, Thanikachalam; Manavalan, Rajappan (Journal of Applied Biomedicine, 2006)
The present study was undertaken to evaluate the possibility of chiral discrimination in the release of enantiomers of ketoprofen (KT) in tablet form and, in turn, the bioavailability of the individual enantiomers, using the rabbit as a model. The enantiomeric concentration of KT in plasma was determined using a customized chiral HPLC analysis. First the plasma concentration-time profile was established for pure (±) KT in order to assess the extent of chiral discrimination. Subsequently the tablet formulation (Rhofenid-100mg) was administered, at a dose equivalent to 10 mg/kg, to assess the enantiospecific bioavailability of KT enantiomers in the rabbit following the same protocol as followed for the pure KT. In vivo studies revealed that the bioavailability of S-KT is higher than that of the Renantiomer, after oral dosing with both KT-tablet and KT-pure. But the degree of chiral discrimination is more pronounced and more statistically significant in the case KT formulation as reflected by the enantioselective pharmacokinetic data. The observations presented in this article further emphasize the significance of differentiating between enantiomers of chiral drugs when assessing bioavailability and correlating efficiency with drug concentration. The study opens up a new avenue to the design of stereoselective dosage forms.
Keywords: Chromatography, High Pressure Liquid; interpretace statistických dat; Tablets; tablety; Biological Availability; Financing, Government; biologická dostupnost; Ketoprofen; ketoprofen; farmakokinetika; Data Interpretation, Statistical; Pharmacokinetics; financování vládou; vysokoúčinná kapalinová chromatografie